Poetics of the Uncanny: A Post-Phenomenological Critique of D. H. Lawrence and Somerset Maugham’s Short Fiction - Umar Shehzad (NUML Journal of Critical Inquiry)
Taking issue with Sigmund Freud’s premise on the subject, this essay seeks alternately to inquire into, challenge, and broaden our understanding of the uncanny. Even though this genius from the field of psychoanalysis is quite right in wreathing the uncanny with the murky aura that it wears to date, his insistence on driving one way traffic from heimlich to das unheimliche while at the same time refusing to let it out of “the realm of the frightening” gives a kind of staleness and fixity to the subject of the uncanny, which is no less than its undoing, especially when it comes to its artistic representation. Eschewing psychoanalytical debates and focusing rather upon the post-phenomenological discourse, I’ll show as to how the homely artistic devices like paradox, reversal, thematic and narrative flux, unswerving matter-of-factness yield an uncanny import in “The Rocking-Horse Winner” and “The Book Bag,” the two short stories by Lawrence and Maugham respectively. Insisting upon the essential uncanniness of art, this article proposes that the uncanny hinges on what Martin Seel (2005) describes as art’s fundamental “irreality” and Theodor Adorno (1973) calls “appearances”. I hypothesize that the uncanny owes its life to a continual movement of the subject matter between openness and closure, between imagination and reality, between the outer world and the inner domain, between what Bhabha (1992) alludes to as the world and the home.